Recent Advances in Breaking Scaling Relations for Effective Electrochemical Conversion of CO2. Issue 17 (29th April 2016) - Li, Yawei; Sun, Qiang
Abstract : The increasing concentration of CO2 in the atmosphere, and the resulting environmental problems, call for effective ways to convert CO2 into valuable fuels and chemicals for a sustainable carbon cycle. In such a context, CO2 electrocatalytic reduction has been hotly studied due to the merits of ambient operational conditions and easy control of the reaction process by changing the applied potential. Among the various systems studied, Cu and Au are found to possess the highest Faradaic efficiency toward cathodic electrocatalytic conversion of CO2 to hydrocarbons and CO, respectively. However, both of them suffer from large overpotentials owing to the limitations imposed by the scaling relations between the carbonaceous adsorbates. Therefore, establishing how to break the scaling relations for effective electrochemical conversion of CO2 has become an urgent research topic. The recent advances in breaking the adsorption energy scaling relations to reduce the overpotential, improve the catalytic activity and suppress the side reaction, are summarized. The origin of the scaling relations, their negative effects on CO2 electrocatalysis, and the strategies for breaking the limitations are discussed. Some suggestions for future study are also proposed. Abstract : The origin of the scaling relations, their negative effects on CO2 electrocatalysis, and the strategies for breaking their limitations to reduce the overpotential, improve the catalytic activity and suppress the side reaction, are discussed.